2003
DOI: 10.1002/chin.200312035
|View full text |Cite
|
Sign up to set email alerts
|

Dirhodium(II) Tetrakis[N‐tetrachlorophthaloyl‐(S)‐tert‐leucinate]: A New Chiral Rh(II) Catalyst for Enantioselective Amidation of C—H Bonds.

Abstract: Enantioselective syntheses Enantioselective syntheses O 0031 Dirhodium(II) Tetrakis[N-tetrachlorophthaloyl-(S)-tert-leucinate]: A New Chiral Rh(II) Catalyst for Enantioselective Amidation of C-H Bonds. -The amidation of benzylic C-H bonds with the phenyliodiane (II) is investigated in the presence of the title compound as catalyst. The observed enantioselectivities are the highest reported to date for Rh-catalyzed C-H amidation. -(YAMAWAKI, M.; TSUTSUI, H.; KITAGAKI, S.; ANADA, M.; HASHIMOTO*, S.; Tetrahedron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…1), 25,32,33 with the tert-leucine derived catalyst Rh 2 (S-PTTL) 4 giving the highest asymmetric induction. [34][35][36][37][38][39][40] This has been further developed by the same group and others to include many other analogs. 25,[41][42][43][44] Müller et al used the same scaffold and emerged with Rh 2 (S-NTTL) 4 as a catalyst derived from N-1,8-naphthaloyl-(S)-tert-leucine.…”
Section: Introductionmentioning
confidence: 99%
“…1), 25,32,33 with the tert-leucine derived catalyst Rh 2 (S-PTTL) 4 giving the highest asymmetric induction. [34][35][36][37][38][39][40] This has been further developed by the same group and others to include many other analogs. 25,[41][42][43][44] Müller et al used the same scaffold and emerged with Rh 2 (S-NTTL) 4 as a catalyst derived from N-1,8-naphthaloyl-(S)-tert-leucine.…”
Section: Introductionmentioning
confidence: 99%
“…Initial attempts to remedy this issue by tailoring the phthalimido groups largely met with failure. Although perhalogenated phthalimides have proven advantageous in many cases, 47 50 the heterobimetallic complex 2b gave almost racemic product. The X-ray structure revealed the likely cause: 2b features an inverted calyx, in which the “chiral” environment envelopes the unreactive Bi(+2) site, whereas the Rh-atom sees the tert -butyl substituents.…”
mentioning
confidence: 99%
“…Out of the large dirhodium(II) catalyst family and by following different approaches for catalyst design, several highly enantioselective dirhodium(II) carboxylate catalysts have been reported to date [13,[35][36][37][38][39][40][41][42][43][44]. Our research group, for example, has recently reported a novel approach for the design of dirhodium(II) tetracarboxylate complexes derived from S-amino acid ligands [35,36,45].…”
Section: Introductionmentioning
confidence: 99%